Sulphomucins favour adhesion of Helicobacter pylori to metaplastic gastric mucosa. - Bravo, J C (1999)
AIMS: To assess the influence of sulphomucin secretion on Helicobacter pylori colonisation and adhesion to metaplastic gastric cells. METHODS: Gastric biopsies from 230 H pylori positive patients with intestinal metaplasia were analysed. Sulphated mucins and H pylori were visualised using a new technique combining high iron diamine-alcian blue mucin stains with the Steiner silver stain for the bacteria. RESULTS: Sulphomucin secretion anywhere in the mucosa and a histological diagnosis of dysplasia increase the risk of H pylori adhesion to metaplastic cells (odds ratios 19.9 and 4.3, respectively). However, only 9.4% of cases showing sulphomucin secretion and 10.8% of cases with dysplasia had evidence of adhesion of H pylori bacteria to metaplastic cells. CONCLUSIONS: The findings suggest that H pylori may play a role in the advanced stages of carcinogenesis. It will be of interest to investigate if the relative small proportion of type III metaplasias that actually progress to carcinoma show persistence of H pylori.